iPhone Design Award-Winning Projects - Dannen, Chris. (Apress, 2010)
This book profiles developers who have received the prestigious Apple Design Award for iPhone app excellence. Youll learn all about what makes these apps truly standout, including explanations of great user interface design and implementation, as well as the code under the hood that makes these the most responsive, intuitive, useful, and just plain fun apps running on the iPhone. Insightful profiles of the developers behind Tweetie, Topple 2, AccuTerra, Postage, and Wooden Labyrinth 3D Detailed explanations of the technical wizardry that makes these apps tick Full-color screenshots and copious downloadable code snippets to get you started building the next iPhone Design Awardwinning apps